PENGARUH KARAKTERISTTK CORPORATE GOVERNANCE TERHAD AP STRUKTUR MODAL - Muhammad Zilal Hamzah; Andhika Suparjan (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2009)
Today, global economics condition has given many changes in national economics situation, especially in business competition. It can be seen from the agents of economics activity either domestic or foreign agent who operated their activities in Indonesia. Hence, every company should have their own characteristic in order to develop their business, if compares to anothers. This research aims to know the effect of corporate governance characteristic on capital structure. With using Ordinary Least Square method, this research finds that Board Size, Board Composition, CEO Duality, CEO Tenure, Firm Size, ROA, Risk, and Growth have significant effect toward their Debt Ratio, simultaneously. Meanwhile, partially Board Size and Growth have no significant effect toward Debt Ratio. As the conclusion, the good corporate governance will increase the value of the firm.Keywords: Corporate Governance, Capital Structure, value of the firm.